Therapeutic Approach to Alzheimer's Disease: Current Treatments and New Perspectives - Teresa Pardo-Moreno; Anabel González-Acedo; Antonio Rivas-Domínguez; Victoria García-Morales; Francisco Jose García-Cozar; Juan Jose Ramos-Rodríguez; Lucía Melguizo-Rodríguez (MDPI AG, 2022)
Alzheimer's disease (AD) is the most common cause of dementia. The pathophysiology of this disease is characterized by the accumulation of amyloid-β, leading to the formation of senile plaques, and by the intracellular presence of neurofibrillary tangles based on hyperphosphorylated tau protein. In the therapeutic approach to AD, we can identify three important fronts: the approved drugs currently available for the treatment of the disease, which include aducanumab, donepezil, galantamine, rivastigmine, memantine, and a combination of memantine and donepezil; therapies under investigation that work mainly on Aβ pathology and tau pathology, and which include γ-secretase inhibitors, β-secretase inhibitors, α-secretase modulators, aggregation inhibitors, metal interfering drugs, drugs that enhance Aβ clearance, inhibitors of tau protein hyperphosphorylation, tau protein aggregation inhibitors, and drugs that promote the clearance of tau, and finally, other alternative therapies designed to improve lifestyle, thus contributing to the prevention of the disease. Therefore, the aim of this review was to analyze and describe current treatments and possible future alternatives in the therapeutic approach to AD.